Numerical Investigation of the Hydrodynamic Forces on Offshore Piggyback Pipelines in Steady Currents - Nazila Kardan (نشریه مهندسی دریا, 2018)
The oil and gas pipelines are considered as one of the most important offshore structures. In this study, the turbulent flow past piggyback pipelines and vortex shedding are numerically simulated under steady currents. Numerical simulation has been conducted for different values of flow velocities, diameter ratios, and gap ratios; in order to investigate how the hydrodynamic forces of the small and large cylinders is affected.  The effects of different parameters as mentioned above on the vortex shedding and the hydrodynamics forces on the cylinders are investigated using the numerical model. Evaluation of the numerical model revealed that the drag coefficient of small and large cylinder increased as the flow velocity is increasing. At the large value of gap ratios, increasing the flow velocity has no effect on RMS lift force of large cylinder whereas the RMS lift force of large and small cylinder considerably increased by decreasing the gap ratio.